Study of properties of welded joint using Dantec’s Istra 4D systems - Domanski, T.; Piekarska, W.; Kubiak, M. (Автоматическая сварка, 2017)
The paper presents displacement and strain fields measured at various stages of tension of flat samples in order to compare the effect of different technological parameters on mechanical properties of welded joints. Results of measurements are also compared with the results of tensile test of the base material to determine the impact of welding process on changes of mechanical properties of tested steel. The measurement of displacements and strains in tensed flat specimens made of S355 steel, hybrid welded using electric arc and laser beam is in the scope of this work. Welding process is performed using Yb:YAG laser and electric arc in GMAW method. D70 Trumpf laser head with maximum power up to 12 kW is used in welding tests with a spot diameter of the laser beam d=0.8 mm. Welded joints are made for different technological parameters of the process with laser beam heat source leading in the tandem. Tension tests of flat samples are performed in accordance with norm PN-EN ISO 6892-1. Dantec Q-400 ISTRA multi-camera 3D correlation system is used for strain and displacement measurements. The method of measurement is based on the correlation of digital images recorded by the three cameras. Surface of tested samples is covered with a layer of white and black paint. The measurement took place by tracking movements of spots covering the surface of the sample, loaded by longitudinal force. Рассмотрен характер смещения и поля деформации, которые были измерены на различных стадиях растяжения плоских образцов с целью сравнения влияния различных технологических параметров на механические свойства сварных соединений. Результаты измерений также сравниваются с результатами испытания на растяжение основного материала, позволяющие оценить влияние процесса сварки на изменения механических свойств испытанной стали. Представлены данные смещений и деформаций в плоских сварных образцах из стали S355, выполненных гибридной сваркой с использованием электрической дуги и лазерного пучка. Процесс сварки выполняся Yb:YAG лазером и электрической дугой при дуговой сварке металлическим электродом в защитном газе. В сварочных испытаниях использовалась лазерная головка D70 Trumpfc максимальной мощностью до 12 кВт и диаметром пятна лазерного пучка d = 0,8 м. Сварные соединения были выполнены для различных технологических параметров процесса. Испытания на растяжение плоских образцов выполняли в соответствии с нормами PN-EN ISO 6891-1. Многокамерная корреляционная 3D система Dantec Q-400 ISTRA использована для измерения деформаций и смещений. Метод измерения основывается на корреляции цифровых изображений, записанных при помощи трех камер. Поверхность испытанных образцов покрывали слоем белой и черной краски. Измерение проводили посредством следящего перемещения за точками, которые покрывают поверхность образца, нагруженного продольным усилием. Розглянуто характер зміщення і поля деформації, які були виміряні на різних стадіях розтягування пласких зразків з метою порівняння впливу різних технологічних параметрів на механічні властивості зварних з’єднань. Результати вимірювань також порівнюються з результатами випробування на розтягнення основного матеріалу, що дозволяють оцінити вплив процесу зварювання на зміни механічних властивостей випробуваної сталі. Представлені дані зсувів і деформацій в пласких зварних зразках зі сталі S355, виконаних гібридним зварюванням з використанням електричної дуги і лазерного пучка. Процес зварювання виконувався Yb:YAG лазером і електричною дугою при дуговому зварюванні металевим електродом в захисному газі. У зварювальних випробуваннях було розроблено лазерну голівку D70 Trumpfc максимальною потужністю до 12 кВт і діаметром плями лазерного пучка d = = 0,8 мм. Зварні з’єднання були виконані для різних технологічних параметрів процесу. Випробування на розтяг пласких зразків виконували відповідно до норм PN-EN ISO 6891-1. Багатокамерна кореляційний 3D система Dantec Q-400 ISTRA використана для вимірювання деформацій і зсувів. Метод вимірювання грунтується на кореляції цифрових зображень, записаних за допомогою трьох камер. Поверхні випробуваних зразків покривали шаром білої і чорної фарби. Вимірювання проводили за допомогою стеження за переміщенням точок, які покривають поверхню зразка, навантаженого поздовжнім зусиллям.